Kebebasan Individu dalam Eksistensialisme dan Implikasinya terhadap Bimbingan dan Konseling - Aurora Putri Adellia (Indonesian Journal of Educational Counseling, 2026)
This study aims to explore the concept of individual freedom from the perspective of existentialist philosophy and its implications for guidance and counseling. The study employs a qualitative method using a literature review approach. Data were collected from books, national journals, and international journals discussing existentialism, individual freedom, the meaning of life, and the existential approach in guidance and counseling. Data analysis was conducted using content analysis. The results of the study indicate that individual freedom is a fundamental concept in existentialism that relates to responsibility, existential anxiety, the formation of self-identity, and the search for the meaning of life. In the digital age, individuals are vulnerable to identity crises and low self-awareness due to the influence of the social environment and digital media. The existential approach in guidance and counseling helps individuals develop self-awareness, understand life choices, take responsibility for the decisions they make, and discover the meaning of life more deeply. These findings underscore the importance of the existential approach as a philosophical foundation in the development of guidance and counseling services.